1987
DOI: 10.1128/mcb.7.10.3527
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a signal for nuclear targeting in platelet-derived-growth-factor-related molecules.

Abstract: The v-vis gene encodes p28sis, the transforming protein of simian sarcoma virus. This gene resulted from a fusion of the env gene of simian sarcoma-associated virus and the woolly monkey gene for the B chain of platelet-derived growth factor (PDGF). Previous work has shown that the v-sis gene product undergoes signal sequence cleavage, glycosylation, dimerization, and proteolytic processing to yield a secreted form of the protein. It transport across the endoplasmic reticulum is blocked by the introduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…In the case of growth factors, recent studies have implicated a positively charged, 7-amino-acid stretch in acidic fibroblast growth factor (aFGF) as responsible for targeting to the nucleus and required for mitogenic activity as well (Imamura et al 1990). There are reports that PDGF can achieve a nuclear location (Lee et al 1987;Yeh et al 1987), and there is evidence that the nuclear targeting signal (Lee et al 1987) corresponds to the region identified by us as a membrane retention domain. Our present studies demonstrate that deletion of this putative nuclear targeting sequence from either chain of PDGF had no effect on its mitogenic properties.…”
Section: Identification Of Pdgf Retention Sequencesmentioning
confidence: 99%
“…In the case of growth factors, recent studies have implicated a positively charged, 7-amino-acid stretch in acidic fibroblast growth factor (aFGF) as responsible for targeting to the nucleus and required for mitogenic activity as well (Imamura et al 1990). There are reports that PDGF can achieve a nuclear location (Lee et al 1987;Yeh et al 1987), and there is evidence that the nuclear targeting signal (Lee et al 1987) corresponds to the region identified by us as a membrane retention domain. Our present studies demonstrate that deletion of this putative nuclear targeting sequence from either chain of PDGF had no effect on its mitogenic properties.…”
Section: Identification Of Pdgf Retention Sequencesmentioning
confidence: 99%
“…Additionally, we noted a similarity between the four residues at the C terminus of the long A chain, LKPT, and a sequence in the B chain, LKET. This LKXT sequence is not required for the nuclear targeting of the B chain (15) and is probably not required for the targeting of the A chain.…”
mentioning
confidence: 99%
“…Plasmids transfected into CV-1 cells by the calcium phosphate procedure were pSV2CAT (A), pDM117 (B), pSV2DHFR (C), pDM118 (D), pAL79 (E), and pAL125 (F). pSV2CAT (11), pSV2DHFR (20), and pAL79 (containing PK [15]) contain the wild-type genes under the control of the simian virus 40 early promoter. The CAT-NTS and PK-NTS fusions have the sequence PRESGKKRKRKRLKPT appended to the C terminus of each protein, and the predicted molecular mass is increased from 25.6 to 27.6 kilodaltons for CAT and from 21.6 to 23.6 kilodaltons for DHFR.…”
mentioning
confidence: 99%
See 2 more Smart Citations